2010
DOI: 10.1080/09613218.2010.494832
|View full text |Cite
|
Sign up to set email alerts
|

Home energy monitors: impact over the medium-term

Abstract: Home Energy Management Systems (Hems), e.g. energy monitors, are intermediary products that can visualize, manage, and/or monitor the energy use of other products or whole households. Hems increasingly receive attention for their role in energy conservation in households. A literature review and a case study examine the mid-term effectiveness (> 4 months) of Hems. The case study present the results of a 15-month pilot with a domestic energy monitor in the Netherlands. It explores the extent to which participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(112 citation statements)
references
References 17 publications
8
103
1
Order By: Relevance
“…On the one hand, feedback effects could be short-lived because household behaviour returns to long-term habits after a certain time. For example, van Dam et al (2010) find that the initial savings of 7.8% in electricity consumption after four months could not be sustained in the medium to long term. On the other hand, if information feedback results in a permanent change in habits, these effects could have a longterm impact on energy use.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, feedback effects could be short-lived because household behaviour returns to long-term habits after a certain time. For example, van Dam et al (2010) find that the initial savings of 7.8% in electricity consumption after four months could not be sustained in the medium to long term. On the other hand, if information feedback results in a permanent change in habits, these effects could have a longterm impact on energy use.…”
Section: Discussionmentioning
confidence: 99%
“…: Grønhøj and Thøgersen, 2011;Hargreaves et al, 2010;2013;Oltra et al, 2014;Strengers, 2011;2013;Rettie et al, 2013;van Dam et al, 2010; also see Buchanan et al, 2014). However, these studies also note a number of constraints on the impacts of IHDs.…”
Section: Research Into the Impact Of Energy Consumption Feedbackmentioning
confidence: 99%
“…When studying the effectiveness of in-home-displays, a typical type of ecofeedback system, Van Dam et al [14] argued that "a onesize-fits-all approach for in-home-displays cannot be justified", which highlights that the performance of ecofeedback systems is dependent on the characteristics of the users. In fact, it has been reported that not all consumers have the potential of saving energy consumption by using eco-feedback system [15].…”
Section: Factors Influencing the Effectiveness Of Eco-feedback Systemsmentioning
confidence: 99%